ANALISIS PENJUALAN DENGAN BAURAN PEMASARAN PADA PERUSAHAAN KATERING DI DAERAH ISTIMEWA YOGYAKARTA - SUTRIYANTI PURWANTI (Jurnal Penelitian Humaniora, 2003)
Abstract The aims this study is to find out the influences of marketing mix to the result of catering sales Survey method is used in this research. The research population is catering companies in Yogyakarta Special religion. The sample measurement is determined based on the iteration formula and gained for about 40 companies. In order to get the samples, stratified random sampling technique is used. The research has two kinds of data, where as to collect the secondary data, documentation used. The analysis uses verivicative method, which is done by using Path analysis technique. The result of Path analysis test shows that, either simultaneously or partially marketing mix (product, price, distribution and promotion) has positive influences on the scale results. From the four elements of marketing mix, distribution has the biggest influences on the sale results. Based on the results of the empirical test, catering companies needs to pay attention on distribution aspects, such as the punctuality of the delivery. The reason is because distribution has the biggest effect on the quantity of the order, which finally can increase the sale results. Keywords: marketing, marketing mix, catering and food sale.